Education for Clean and Healthy Lifestyle (PHBS) at Budi Utama Kerobokan Junior High School - Arista, Cindy; Harianti, Ayuni (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The covid-19 pandemic has had an impact on the education sector in Indonesia, since March 2019 education at all levels has been carried out online. Various problems arose during the distance learning process, so the government issued a Joint Decree of 4 Ministers regarding the implementation of face-to-face learning, the central government has authorized local governments to permit face-to-face learning in 2021. As a form of community service from The Bali Nahdlatul Ulama Institute of Science and Technology carried out PHBS educational activities as an effort to anticipate the spread of Covid-19 in the Budi Utama Kerobokan Junior High School. The methods used are counseling, distribution of information brochures, regarding PHBS and efforts to prevent Covid-19, as well as training and mentoring PHBS in the school environment. Based on the results of the evaluation, data obtained from questionnaires to 65 respondents consisting of students, teachers, and school residents as much as 100% have complied with health protocols in the school environment and 95.4% have implemented the PHBS movement in schools (Figure 4). This training activity is expected to increase the knowledge and awareness of school residents and the surrounding community in anticipating the spread of Covid-19 in the school environment, complying with applicable health protocols, and creating a clean and healthy school environment. Key words: Face-to-face Learning; Covid-19 health protocol; PHBS educational activities.